Shackleton's boat journey : the narrative from the Captain of the 'Endurance' - Worsley, Frank Arthur, 1872-1943 (Narrative Press, 2001)
Shackleton's 1914 Antarctic expedition was trapped when their ship became stuck in pack ice. This is the captain's version of this remarkable journey.